2020
DOI: 10.1039/d0tb00614a
|View full text |Cite
|
Sign up to set email alerts
|

14N–1H HMQC solid-state NMR as a powerful tool to study amorphous formulations – an exemplary study of paclitaxel loaded polymer micelles

Abstract: 14N–1H HMQC experiments are powerful experiments to characterize amorphous drug–polymer formulations of paclitaxel yielding well-separated signals in the 14N dimension as well as information on the symmetry of 14N and 14N–1H interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…They enable fast characterization of pharmaceutical compounds and formulation by probing API–polymer interaction, allowing NMR crystallography approaches and understanding of low drug-loaded formulation . The 14 N– 1 H heteronuclear multiple-quantum coherence (HMQC) experiment carried out at the high magnetic field and at ultrafast MAS conditions under direct 1 H signal detection has been robustly employed to probe interactions in crystalline systems , and recently to highlight molecular association and interactions in amorphous dispersions. , 14 N– 1 H HMQC spectra were used to identify hydrogen bonding interaction in a nicotinamide palmitic acid cocrystal and acetaminophen–PVP amorphous dispersion . The versatility of this experiment was demonstrated by providing information on the symmetry of the nitrogen environment and through-space proximities in paclitaxel-loaded polymer micelles amorphous formulations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They enable fast characterization of pharmaceutical compounds and formulation by probing API–polymer interaction, allowing NMR crystallography approaches and understanding of low drug-loaded formulation . The 14 N– 1 H heteronuclear multiple-quantum coherence (HMQC) experiment carried out at the high magnetic field and at ultrafast MAS conditions under direct 1 H signal detection has been robustly employed to probe interactions in crystalline systems , and recently to highlight molecular association and interactions in amorphous dispersions. , 14 N– 1 H HMQC spectra were used to identify hydrogen bonding interaction in a nicotinamide palmitic acid cocrystal and acetaminophen–PVP amorphous dispersion . The versatility of this experiment was demonstrated by providing information on the symmetry of the nitrogen environment and through-space proximities in paclitaxel-loaded polymer micelles amorphous formulations .…”
Section: Introductionmentioning
confidence: 99%
“…The 14 N– 1 H heteronuclear multiple-quantum coherence (HMQC) experiment carried out at the high magnetic field and at ultrafast MAS conditions under direct 1 H signal detection has been robustly employed to probe interactions in crystalline systems , and recently to highlight molecular association and interactions in amorphous dispersions. , 14 N– 1 H HMQC spectra were used to identify hydrogen bonding interaction in a nicotinamide palmitic acid cocrystal and acetaminophen–PVP amorphous dispersion . The versatility of this experiment was demonstrated by providing information on the symmetry of the nitrogen environment and through-space proximities in paclitaxel-loaded polymer micelles amorphous formulations . The 14 N– 1 H HMQC experiment has however, to the best of our knowledge, not been used so far to investigate API–polymer interactions in HPMC-AS-based amorphous formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, 14 N‐ 1 H heteronuclear multiple‐quantum correlation (HMQC) solid‐state NMR was employed to study the interactions of amide groups in polymer and drug molecules. [ 173 ] In comparison to neat polymer and PTX, the formulations exhibited decreasing in 14 N quadrupolar shift at negative values, which suggests a more symmetric nitrogen environment. The authors assigned these spectral changes to the tertiary amides of POx in a close proximity of PTX molecules serving as hydrogen bond acceptors, leading to the more symmetric nitrogen environment.…”
Section: Poly(2‐oxazoline)‐based Nanoformulationsmentioning
confidence: 99%
“…Worm-inhibiting drugs paclitaxel and vismodegib contain numerous electronegative and hydrogen bond-accepting groups that may strengthen their interaction with the poly(2-oxazoline). Notably, NMR spectra previously suggested that paclitaxel can interact with the amide bond motif of both poly(2-methyl-2-oxasoline) and poly(2-butyl-2-oxasoline) [11] . Therefore, such drugs can bind to the same binding sites that RD binds to and may result in the displacement of the dye if their binding affinity exceeds that of RD.…”
Section: Probing Drug Effects On the Micelle Microenvironment By Reichardt's Dyementioning
confidence: 99%